Development of the Greek version of the Face Name Associative Memory Exam (GR-FNAME12) in cognitively normal elderly individuals. (30th November 2018) - Kormas, Constantinos; Megalokonomou, Anastasia; Zalonis, Ioannis; Evdokimidis, Ioannis; Kapaki, Elisabeth; Potagas, Constantin
Abstract: Objective: The Face–Name Associative Memory Examination (FNAME) is a cross-modal associative memory test with a high sensitivity for detecting Alzheimer's disease-related subtle memory problems at an early preclinical stage. The present study examined the psychometric characteristics of a Greek version of the short form of FNAME (GR-FNAME12) to evaluate the contribution of demographic characteristics, report the range of performance within our sample, and estimate regression-based norms in cognitively normal elderly individuals.Method: In all, 216 cognitively normal elderly individuals were recruited and were administered a version of the short form of the FNAME (GR-FNAME12) that was culture and language specific to Greek-speaking individuals and developed for this study.Results: The construct validity of GR-FNAME12 was determined using principal component analysis thereby revealing two factors: face–name and face–occupation. These match the original version of the test. A significant positive correlation between GR-FNAME12 and two traditional memory measures – the RAVLT and the ROCFT – supported convergent validity. Test–retest reliability was computed for 32 participants. Multiple regression analyses showed that only age and not education or gender significantly predicted performance on the GR-FNAME12. We also estimated regression-based norms for the GR-FNAME12 scales.Conclusion: It was found that the Greek version of the FNAME12 had adequate psychometric properties, and could be administered to Greek-speaking individuals for clinical and research purposes.